Daidalotarsonemus and Excelsotarsonemus species (Acari: Tarsonemidae) found in shaded cacao plantations in Brazil, with a description of a new species - Sousa, André Silva Guimarães; Rezende, José Marcos [UNESP]; Lofego, Antonio Carlos [UNESP]; Ochoa, Ronald; Oliveira, Anibal Ramadan (Taylor & Francis, 2018)
Mites of the family Tarsonemidae (Acari: Prostigmata) exhibit a great diversity of feeding habits including fungivorous, algivorous, plant feeders, and predatory of other mites, as parasitoids and parasites are kinds of symbionts of other insects. They also have a considerable diversity of morphological structures, including the shape and structure of the mouthparts and specialized tactile organs, particularly the setae on the body and legs. The Atlantic Forest remnant is considered to be a very diverse tropical biota. Samples were collected on Theobroma cacao and Artocarpus heterophyllus trees in cabruca agroforest systems located in Ilhéus, Bahia State, Brazil. A new species, Excelsotarsonemus cabrucae Sousa, Lofego & Ochoa, sp. n. is described and illustrated. Six Daidalotarsonemus and three Excelsotarsonemus species were identified in the same area. A key to the species of Daidalotarsonemus of Brazil and a key to the species of Excelsotarsonemus of the world are presented. The findings emphasize the importance of conducting mite surveys in rainforests to better understand the mite diversity which inhabits this biome.http://www.zoobank.org/urn:lsid:zoobank.org:act:15D43DCE-E281-456F-B218-6F0947B6EA04.
Keywords: Atlantic Forest; cabruca; systematic; Tarsonemoidea; taxonomy